Whole-body vibration exposure in sport: four relevant cases - Tarabini, M.; Saggin, B.; Scaccabarozzi, D. (Ergonomics, 2015)
This study investigates the whole-body vibration exposure in kite surfing, alpine skiing, snowboarding and cycling. The vibration exposure was experimentally evaluated following the ISO 2631 guidelines. Results evidenced that the most critical axis is the vertical one. The weighted vibration levels are always larger than 2.5 m/s^2 and the vibration dose values are larger than 25 m/s^1.75. The exposure limit values of the EU directive are reached after 8-37 min depending on the sport. The vibration magnitude is influenced by the athletes` speed, by their skill level and sometimes by the equipment. The large vibration values suggest that the practice of sport activities may be a confounding factor in the aetiology of vibration-related diseases.